Academic, Financial and Administrative Issues of Online Teaching During Corona Pandemic: The Scenario of Private Universities in Bangladesh - Hasan, Zulfiqar; Islam, K. M. Anwarul (International Journal of Accounting & Finance Review, 2020)
Regarding financial and administrative issues involved in online teaching, the study focuses on the views of the teachers of private universities in conducting online classes during the corona pandemic in Bangladesh. Based on primary data collected from teachers of 22 private universities selected randomly, study finds some reasons for online classes like financial needs and obligations of the university to pay the salaries and other allowances by collecting tuition fees from the students, to save the academic year of the students, to follow the directives of the UGC and Government, etc. The study also finds some significant differences in the uses of technology, internet, and equipment by the teachers before and during the corona pandemic. Online teaching has significant effects on teachers’ training, student’s punctuality in attending classes, interactions between teachers & students. It also helps authority in monitoring the classes. Finally, the study recommends some policy guidelines for the University Owners & authorities, Government, UGC, and the faculty members as well. JEL Classification: A23, M41.